Furniture shop management system - Huey Ning, Chan (2011)
This thesis in title "Furniture Shop Management System" which is a shop management system to manage furniture shop business and it is implemented with inventory management.There are 4 main modules in this system,which are profile management,inventory management,sales management and financial management.The problem statements of this thesis are the current management system does not have well inventory management. There does not have the facilities to handle the receipts and issues of stock.The second problem is this current management system is manually system which records the information of staff and supplier, stock record, and sales report in paperwork.There are two (2) objectives of this thesis,which are to develop a systematic inventory management of Furniture Shop Management System (FSMS) and to provide a good storage stock and retrieve data information in this furniture shop management system.This thesis is discussed on how this furniture shop management system to be implemented, the tools and programming languages used,and the resources needed in developing this system.Prototyping is used to develop this project.There are 8 phases which are initial requirements,design,prototyping,customer evaluation, review and update,development,test and maintain.The strength of FSMS is implemented with the well inventory management to manipulate the inventory of the shop.The status stock level will be notified to the user automatically.This thesis had been successfully completed and the system is successfully developed and function able.